Analisis Pelaksanaan Operasi Pemeliharaan (OP) Daerah Irigasi Wuno Terhadap Tingkat Pendapatan Petani Sawah Desa Sidera Kecamatan Sigi Biromaru Kabupaten Sigi - Sulfiati, Sulfiati; Tahir, Suratnan (Siimo Engineering, 2020)
This study aims to evaluate the implementation of the regional irrigation of Wuno to increase the rice farmers income in Sidera Village in Biromaru Sigi District. The research is categorised as a survey study with explanatory method. There are 30 samples (14 %) out of the 210 of total population in 7 group of farmers. Elements are used to evaluate is supported by maintenance operation with Product Exhaustion Theorem method, and revenue. The results show that 1) Discharge of water needed to sustain the agricultural production in Sidera village with water calculation value is equal to 13,746,967 liters/seconds/paddy farmers. The large amount of discharge required by each rice farmers to irrigate their land can not be fulfilled simultaneously. Therefore, the distribution of water should be held by rotation. 2) The allocation of funds for maintenance operation in Wuno irrigation shows a critical role to improve the rice production in Sidera village in Sigi Biromaru district. Although, the implementation requires considerable cost which is about Rp. 156,230,000,-. It includes roughly 67,50 % for operating costs and 32,5 % for maintenance costs. A substantial amount is covered only 1.34 % by P3A contribution. It means that the rest of 98,66 % must be available each year for the allocation of maintenance operation of Wuno irrigation, 3) the impact of irrigation on agricultural production of rice farmers in Sidera village will increase the rice production. In this case, the condition of Wuno irrigation were properly maintained to provide adequate water supply for the needs of paddy rice field. The high production will also affect the level ofrice farmers income, even their spending for fertilizers, liquid medicines, and labor are also increase. 4) From the average land area of 0.86 hectares, the rice farmers earn an average revenue of Rp. 9,411,066.67,-. The average is categorised as gross profit before deducting all of its total expenses. This result is obtained by adding of the variable costs and the cost of cash. So, water rent roughly Rp 5.075.166,67,- after deducting all the costs. The results of the study stated that the implementation of the Wuno regional irrigation has positive effect for increasing the income of rice farmers in Sidera village. This study also suggest that the implementation needs policy intervention to optimize the contribution of the Wuno irrigation area with the aim to increase and sustain the production as well as the income of rice farmers in Sidera village